Estrategia para la Apropiación de Conocimiento Aplicado a la Formación por Competencias en la Educación Superior (2019)
The methodological elements that allow the development of competences in the classroom are established. For the validation of the proposed methodological elements, two institutions of higher education are taken as study cases. In the first institution (A) a first-semester course in the area of Economic Sciences is taken as a reference, and in the second institution (B) a sixth semester course of the Engineering faculty is taken as a reference. The densification concentrated in the higher valuation indexes for the periods where the proposed elements are applied is determined using the statistical model of Gaussian distribution. It is concluded that the elements that have greater influence in the application of the model by competences are the integration of the institutional educational project in the methodology and the participation of the knowledge actors through collaborative work. © 2019, Centro de Informacion Tecnologica.